Nanocellulose, the Green Biopolymer Trending in Pharmaceuticals: A Patent Review - Keth Ribeiro Garcia; Ruy Carlos Ruver Beck; Rosmary Nichele Brandalise; Venina dos Santos; Letícia Scherer Koester (MDPI AG, 2024)
The use of nanocellulose in pharmaceutics is a trend that has emerged in recent years. Its inherently good mechanical properties, compared to different materials, such as its high tensile strength, high elastic modulus and high porosity, as well as its renewability and biodegradability are driving nanocellulose's industrial use and innovations. In this sense, this study aims to conduct a search of patents from 2011 to 2023, involving applications of nanocellulose in pharmaceuticals. A patent search was carried out, employing three different patent databases: Patentscope from World Intellectual Property Organization (WIPO); Espacenet; and LENS.ORG. Patents were separated into two main groups, (i) nanocellulose (NC) comprising all its variations and (ii) bacterial nanocellulose (BNC), and classified into five major areas, according to their application. A total of 215 documents was retrieved, of which 179 were referred to the NC group and 36 to the BNC group. The NC group depicted 49.7%, 15.6%, 16.2%, 8.9% and 9.5% of patents as belonging to design and manufacturing, cell culture systems, drug delivery, wound healing and tissue engineering clusters, respectively. The BNC group classified 44.5% of patents as design and manufacturing and 30.6% as drug delivery, as well as 5.6% and 19.4% of patents as wound healing and tissue engineering, respectively. In conclusion, this work compiled and classified patents addressing exclusively the use of nanocellulose in pharmaceuticals, providing information on its current status and trending advancements, considering environmental responsibility and sustainability in materials and products development for a greener upcoming future.